Long-Term Retrospective Analysis of Re-do Microvascular Decompression in Patients With Hemifacial Spasm - Liu, Jiayu; Li, Fang; Wu, Guangyong; Liu, Bo; Zhou, Jingru; Fan, Cungang; Jiao, Feng; Wang, Dongliang; Wu, Gang; Song, Haidong; Liu, Ruen (Frontiers in Neurology, 2021)
Objective: To explore the clinical characteristics of patients with persistent or recurrent hemifacial spasm (HFS) and the experience of microvascular decompression (MVD) in the treatment of such patients to accumulate additional clinical evidence for optimal treatment protocols. Methods: We retrospectively analyzed the clinical data, surgical methods and treatment efficacies of 176 patients with persistent or recurrent HFS from January 2009 to January 2018. Results: Missing compression zones was the main reason for symptom persistence (87.50%) or recurrence (71.50%) after MVD treatment of HFS. We divided the surgical area into three zones. Most persistent or recurrent cases had decompression only in the root exit zone (REZ) (Zone 1) but missed the ventrolateral pons-involved area (Zone 2) or the bulbopontine sulcus-involved area (Zone 3) in the first MVD. Too much use of Teflon (12.50%), arachnoid adhesions (5.60%) and Teflon granulomas (10.40%) can also cause a recurrence. The difference between preoperative and postoperative Cohen scores was statistically significant in persistent or recurrent HFS patients (p<0.05). The postoperative follow-up time ranged from 36 to 108 months (71.75 ± 22.77). Conclusions: MVD should be performed in the compression site, which is mostly located at the brainstem/facial REZ. Intraoperative exploration should be conducted in accordance with the abovementioned zones to effectively avoid missing offending vessels. Re-do MVD is effective in patients with persistent or recurrent HFS.